2019
DOI: 10.1103/physrevfluids.4.054001
|View full text |Cite
|
Sign up to set email alerts
|

Flow field around a confined active droplet

Abstract: We present here first-of-a-kind experimental measurements of the flow field around a swimming water droplet, using confocal PIV in three dimensions. The droplet is denser than the continuous oil phase, and swims close and parallel to the bottom wall. The measured flow field is first quantitatively characterized and compared to the flow field obtained for an axisymmetric swimmer in unbounded flow. Important qualitative differences are observed, in particular the emergence of a strong isotropic radial flow field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…Given the characteristic size and velocities of confined phoretic microswimmers (de Blois et al. 2019; Lippera et al. 2020 b ; Hokmabad et al.…”
Section: Phoretic Self-propulsion In a Capillarymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the characteristic size and velocities of confined phoretic microswimmers (de Blois et al. 2019; Lippera et al. 2020 b ; Hokmabad et al.…”
Section: Phoretic Self-propulsion In a Capillarymentioning
confidence: 99%
“…Recent experimental measurements have shown significant modifications of the flow field around the droplet when placed close to or between rigid walls (de Blois et al. 2019), and theoretical modelling unveiled the non-trivial alterations of the hydrochemical coupling induced by confinement (Lippera et al. 2020 b ).…”
Section: Introductionmentioning
confidence: 99%
“…well-developed toolbox for tuning their motility, flow generation, and collective dynamics, and solving microfluidic mazes [57][58][59][60][61][62][63][64][65][66][67][68].…”
mentioning
confidence: 99%
“…The activity A and mobility M coefficients characterise the physico-chemical properties of the particle surface and can be positive or negative; from these, a characteristic phoretic velocity scale can be defined as V = |AM|/D. Given the characteristic size and velocities of confined phoretic microswimmers [28,37,38], the fluid and colloid inertia can be neglected, i.e. the Reynolds number Re = ρVa/η is negligible, so that the motion of the particle can be described using the steady Stokes equations.…”
Section: Phoretic Self-propulsion In a Capillarymentioning
confidence: 99%
“…confocal microscopy 28], theoretical models most often ignore the presence of confining boundaries and focus on droplets in unbounded fluid domains, leaving unexplored their role on the emergence and persistence of self-propulsion. Recent experimental measurements have shown significant modifications of the flow field around the droplet when placed close to or between rigid walls [37], and theoretical modelling unveiled the non-trivial alterations of the hydro-chemical coupling induced by confinement [38]. Beyond the influence of a single flat wall, recent experiments have also shown that self-sustained motion can also occur in strongly-confined settings, such as small capillary tubes [34,39].…”
Section: Introductionmentioning
confidence: 99%